Short films remembering the Galley Slaves - Fekete, Ágnes (Acta Neerlandica, 2026)
In the years of 2020–2021 I made a few short films with some people – one touristorganizer and four preachers – who have found it important to preserve the memory ofHungarian galley slaves. In this report, I would like to show the responsibility, respect andlove that the commemorators had for their ancestors, which spirit of this activity was alsoradiated to me.